Nanodisc-Forming Scaffold Protein Promoted Retardation of Amyloid-Beta Aggregation. Issue 21 (19th October 2018) - Sahoo, Bikash Ranjan; Genjo, Takuya; Cox, Sarah J.; Stoddard, Andrea K.; Anantharamaiah, G.M.; Fierke, Carol; Ramamoorthy, Ayyalusamy
Abstract: Peptidic nanodiscs are useful membrane mimetic tools for structural and functional studies of membrane proteins, and membrane interacting peptides including amyloids. Here, we demonstrate anti-amyloidogenic activities of a nanodisc-forming 18-residue peptide (denoted as 4F), both in lipid-bound and lipid-free states by using Alzheimer's amyloid-beta (Aβ40) peptide as an example. Fluorescence-based amyloid fibrillation kinetic assays showed a significant delay in Aβ40 amyloid aggregation by the 4F peptide. In addition, 4F-encased lipid nanodiscs, at an optimal concentration of 4F (>20 μM) and nanodisc size (<10 nm), significantly affect amyloid fibrillation. A comparison of experimental results obtained from nanodiscs with that obtained from liposomes revealed a substantial inhibitory efficacy of 4F-lipid nanodiscs against Aβ40 aggregation and were also found to be suitable to trap Aβ40 intermediates. A combination of atomistic molecular dynamics simulations with NMR and circular dichroism experimental results exhibited a substantial change in Aβ40 conformation upon 4F binding through electrostatic and π–π interactions. Specifically, the 4F peptide was found to interfere with the central β-sheet-forming residues of Aβ40 through substantial hydrogen, π–π, and π–alkyl interactions. Fluorescence experiments and coarse-grained molecular dynamics simulations showed the formation of a ternary complex, where Aβ40 binds to the proximity of peptidic belt and membrane surface that deaccelerate amyloid fibrillation. Electron microscopy images revealed short and thick amyloid fibers of Aβ40 formed in the presence of 4F or 4F-lipid nanodsics. These findings could aid in the development of amyloid inhibitors as well as in stabilizing Aβ40 intermediates for high-resolution structural and neurobiological studies. Graphical Abstract: Highlights: Apolipoprotein mimetic 4F peptide retards beta-amyloid aggregation. 4F nanodiscs substantially inhibit beta-amyloid fibrillation growth. Beta-amyloid forms short and thick fibers in the presence of 4F or 4F nanodiscs. Structural study reveals a ternary association between Aβ40 and 4F nanodiscs.